Audit Ethics as A Moderating Variable in Auditor Quality Assessment - Panji Putranto (Journal La Sociale, 2023)
Urban regions face numerous challenges in implementing regional autonomy. The smart city concept has been implemented by cities in various countries to tackle these issues. This article aims to comprehend and assess the political laws selected by the Indonesian government to address the challenges of implementing regional autonomy in urban areas using smart city concepts and indicators. The research method employed was normative research through a statutory regulations approach, in addition to a conceptual approach. The research material was secondary data comprising primary legal materials as well as secondary legal materials amassed via online and offline research at the library. The data was then analyzed in a descriptive manner. The analysis results demonstrate that numerous Indonesian cities have introduced smart city indicators. However, these indicators lack a legal foundation referencing smart city standards. The absence of specific regulations for smart cities in Indonesia has resulted in unstructured and immeasurable implementation. In Indonesia, the closest legal regulations or policies to the concept of a smart city are those outlined in Government Regulation Number 38 of 2017 concerning Innovation. Going forward, it is necessary to establish legal guidelines that contain specific standards for smart cities, from inception to implementation, in order to enhance regional autonomy in urban areas.